E6C15 (E = Si–Pb): polycyclic aromatic compounds with three planar tetracoordinate carbons. Issue 94 (7th November 2022) - Inostroza, Diego; Leyva-Parra, Luis; Vásquez-Espinal, Alejandro; Contreras-García, Julia; Cui, Zhong-Hua; Pan, Sudip; Thimmakondu, Venkatesan S.; Tiznado, William
Abstract : A systematic exploration of the potential energy surface reveals two global minima with three planar tetra coordinate carbons (ptCs) and two global minima with three quasi-ptCs for E6 C15 (E = Si–Pb) combinations. Abstract : A systematic exploration of the potential energy surface reveals two global minima with three planar tetra coordinate carbons (ptCs) and two global minima with three quasi-ptCs for E6 C15 (E = Si–Pb) combinations. These consist of aromatic polycyclic templates suitable for further design of different materials without hindering the ptC texture.